Enhancing Students' Understanding of Akidah and Akhlak through Competency-Based Learning Models at MI Muhammadiyah Kupang Karangdowo Klaten: A Classroom Action Research - Indayani; Erlina Maghfiroh (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to explore the effectiveness of competency-based learning models in enhancing students' understanding of Akidah and Akhlak at MI Muhammadiyah Kupang Karangdowo Klaten. The research focuses on developing students' moral and religious values through structured learning outcomes that emphasize competencies in Islamic faith and behavior. The study was conducted with 5th-grade students, using competency-based approaches that align with the curriculum objectives of Islamic Education. The primary goal of this research is to assess how well competency-based learning models can foster both cognitive and affective aspects of students' learning in Akidah and Akhlak. The research was implemented in two cycles, with each cycle consisting of planning, action, observation, and reflection. In each cycle, specific learning activities were designed to align with key competencies, such as understanding core Islamic teachings, demonstrating positive character traits, and applying Islamic values in everyday life. Data was collected through student assessments, observations, and teacher reflections to evaluate the effectiveness of the competency-based learning approach in enhancing students' understanding of Akidah and Akhlak. The findings indicate that competency-based learning models significantly improved students' understanding of the material, as well as their ability to apply religious and moral teachings in their daily behavior. Students showed increased engagement and a deeper understanding of both the theoretical and practical aspects of Akidah and Akhlak. The research highlights the importance of using competency-based learning to strengthen religious education by focusing on measurable learning outcomes.